Anaphylaxis: knowledge among oral and maxillofacial surgeons (Research, Society and Development, 2020)
The aim of the present study was to evaluate knowledge regarding the conduct and adequate management of anaphylaxis on the part of oral-maxillofacial surgeons. A quantitative evaluation was performed through a cognitive survey on the subject. The sample was composed of 104 specialists and who participated in the Brazilian Oral-Maxillofacial Surgery and Traumatology Conference. A total of 31.7% of the interviewees were unaware of any protocol for anaphylaxis. Among those with information on the subject, the majority (78.8%) reported that adrenaline is the main drug for the treatment of anaphylaxis, but 50% of these individuals did not know the correct dosage and only 35.6% reported that intramuscular administration was the proper route. Only 12.5% reported having witnessed a case of anaphylaxis and all such cases were resolved with a favorable outcome. A considerable number of surgeons (34.6%) reported not having any drug for emergency care in their offices, but the majority (71.2%) reported being capable of administering such drugs. The present findings revealed a lack of knowledge on the part of many oral-maxillofacial surgeons regarding anaphylactic reactions and treatment.